The effect of good corporate governance on company value in LQ45 companies listed on the Indonesia Stock Exchange - Marissa, Marissa; Isnurhadi, Isnurhadi; Widiyanti, Marlina; Fu’adah, Luk Luk (International research journal of management, IT and social sciences, 2024)
This study aims to analyze the effect of Good Corporate Governance (GCG) on firm value in LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. GCG is proxied through managerial ownership, institutional ownership, audit committee, and independent board of commissioners, while firm value is measured using Tobin’s Q. The research method used purposive sampling with a sample of 19 companies. The data were analyzed using multiple linear regression through SPSS software version 25. The results showed that: (1) managerial ownership has a positive but insignificant effect on firm value, (2) institutional ownership has a significant positive effect on firm value, (3) independent board of commissioners has a significant negative effect on firm value, and (4) audit committee has no significant effect on firm value. These results indicate that GCG implementation still varies in influencing firm value in Indonesia.